The growth performance of growing pigs during feed restriction and re-alimentation in a humid tropical environment - S. O. C. Ugwu; A. E. Onyimonyi (African Journal of Pig Farming, 2015)
Thirty two crossbred (large white x landrace) pigs were used in a 56 days restriction and 56 days re-alimentation study to evaluate the effect of restricting growing pigs at 90, 80 and 70% of the ad libitum feed intake of the control. The pigs averaged 35.23 ± 0.560 kg at the start of the study. There were four treatments (control, 90, 80 and 70%). Each treatment had eight pigs allotted to 2 replications of four pigs each. The pigs received a 16% crude protein and 12.08 MJME/kg diet. Results indicated that average daily gains (ADG) of the control pigs were significantly superior to the others during the restriction period. However, at the end of the 56 days re-alimentation, pigs on the 80% and 70% feeding regime had superior ADG than the pigs on the control and 90 percent feeding regime. Data on the body length (BL) and height at shoulders (HS) followed the same trend as observed for ADG. Feed intakes of pigs were significantly affected during the restriction and re-alimentation period. There was a significant (p < 0.05) decrease in feed intake as level of restriction increased. Also, during re-alimentation pigs on the 70% level had the highest feed intake. Pigs on the 80% level of restriction had the best feed cost/kg gain values at restriction and realimentation. It is concluded that restricting growing pigs at 80% of the ad libitum intake of the control yields best performance and economic benefit.